An ILP based heuristic for a generalization of the post-enrollment course timetabling problem. (December 2016) - Méndez-Díaz, Isabel; Zabala, Paula; Miranda-Bront, Juan José
Abstract: We consider a new timetabling problem arising from a real-world application in a private university in Buenos Aires, Argentina. In this paper we describe the problem in detail, which generalizes the Post-Enrollment Course Timetabling Problem (PECTP), propose an ILP model and a heuristic approach based on this formulation. This algorithm has been implemented and tested on instances obtained from real data, showing that the approach is feasible in practice and produces good quality solutions. Abstract : Highlights: We tackle a difficult optimization problem, arising from a real world application. We define a new problem in the context of the university timetabling problems. The problem generalizes two other problems from the related literature. We propose an ILP formulation and develop a heuristic algorithm based on this model. The algorithm is used in practice, providing good quality results.